Taonga, Rights and Interests: Some Observations on WAI 262 and the Framework of Protections for the Māori Language - Stephens, Māmari (Victoria University of Wellington Law Review, 2011)
In October 2010 the Waitangi Tribunal released the first chapter of its long-awaited report of the WAI 262 enquiry into indigenous flora and fauna and Māori intellectual property. This chapter focuses on aspects of the claim relating to the Māori language and critiques the development of Māori and Crown generated initiatives to protect and revitalise te reo Māori, including the Māori Language Strategy (Te Rautaki Reo Māori). The Tribunal argues that the Crown must ultimately become Māori speaking. Consideration of this report and the legal protections in place for the Māori language reveals a framework that is incoherent, and largely incapable of achieving the Tribunal’s goal, or even of fully protecting what the Tribunal described as "a taonga of quite transcendent importance".